Ascher syndrome - Ajitesh Prakash Varshney; Pratik Gahalaut; Nitin Mishra; Madhur Kant Rastogi (Wolters Kluwer Medknow Publications, 2019)
The triad of blepharochalasis, double lip, and nontoxic thyroid enlargement characterizes Ascher syndrome. We describe the case of a 16-year-old female who presented with progressive laxity and swelling of the skin associated with recurrent progressive episodes of painless swelling of the eyelids with increase in the size of the upper lip and diffuse swelling over the neck. We discuss this case for rarity of its presentation in the Indian population.